Chronic lung disease in children and adolescents with HIV: a case–control study. Issue 5 (10th February 2020) - McHugh, Grace; Rehman, Andrea M.; Simms, Victoria; Gonzalez‐Martinez, Carmen; Bandason, Tsitsi; Dauya, Ethel; Moyo, Brewster; Mujuru, Hilda; Rylance, Jamie; Sovershaeva, Evgeniya; Weiss, Helen A.; Kranzer, Katharina; et al.
Abstract: Objective: To describe the features of HIV‐associated chronic lung disease (CLD) in older children and adolescents living with HIV and to examine the clinical factors associated with CLD. This is a post hoc analysis of baseline data from the BREATHE clinical trial (ClinicalTrials.gov, NCT02426112). Methods: Children and adolescents aged 6–19 years were screened for CLD (defined as a FEV1 z ‐score <−1 with no reversibility post‐bronchodilation with salbutamol) at two HIV clinics in Harare, Zimbabwe, and Blantyre, Malawi. Eligible participants with CLD (cases) were enrolled, together with a control group without CLD [frequency‐matched by age group and duration on antiretroviral therapy (ART)] in a 4:1 allocation ratio. A clinical history and examination were undertaken. The association between CLD and a priori ‐defined demographic and clinical covariates was investigated using multivariable logistic regression. Results: Of the 1585 participants screened, 419 (32%) had a FEV1 z ‐score <−1, of whom 347 were enrolled as cases [median age 15.3 years (IQR 12.7–17.7); 48.9% female] and 74 with FEV1 z ‐score >0 as controls [median age 15.6 years (IQR 12.1–18.2); 62.2% female]. Among cases, current respiratory symptoms including cough and shortness of breath were reported infrequently (9.3% and 1.8%, respectively). However, 152 (43.8%) of cases had a respiratory rate above the 90th centile for their age. Wasting and taking second‐line ART were independently associated with CLD. Conclusions: The presence of CLD indicates the need to address additional treatment support for youth living with HIV, alongside ART provision, to ensure a healthier adulthood. Abstract : Objectif: Décrire les caractéristiques de la maladie pulmonaire chronique (MPC) associée au VIH chez les enfants plus âgés et les adolescents vivant avec le VIH et examiner les facteurs cliniques associés à la MPC. Il s'agit d'une analyse post‐hoc des données de référence de l'essai clinique BREATHE (ClinicalTrials.gov, NCT02426112 ). Méthodes: Les enfants et adolescents âgés de 6 à 19 ans ont été dépistés pour la MPC (défini comme un score z FEV1 <‐1 sans réversibilité post‐bronchodilatation avec du salbutamol) dans deux cliniques VIH à Harare, au Zimbabwe et à Blantyre, au Malawi. Les participants éligibles atteints de MPC (cas) ont été inscrits, ainsi qu'un groupe témoin sans MPC (fréquence appariée par groupe d'âge et durée sous ART) dans un rapport d'allocation de 4:1. Une histoire clinique et un examen ont été entrepris. L'association entre la MPC et les covariables démographiques et cliniques définies a priori a été étudiée en utilisant une régression logistique multivariable. Résultats: Sur les 1.585 participants dépistés, 419 (32%) avaient un score z FEV 1 <‐1, dont 347 étaient inscrits comme cas (âge médian 15, 3 ans [IQR 12, 7 ‐17, 7]; 48, 9% de sexe féminin), et 74 avec un score z FEV1 >0 comme témoins (âge médian 15, 6 ans [IQR 12, 1 ‐18, 2]; 62, 2% de sexe féminin). Parmi les cas, les symptômes respiratoires en cours, y compris la toux et l'essoufflement, n'ont pas été rapportés fréquemment (9, 3% et 1, 8%, respectivement). Cependant, 152 (43, 8%) des cas avaient une fréquence respiratoire supérieure au 90 e centile pour leur âge. L'émaciation et la prise d'un traitement antirétroviral (ART) de deuxième intention étaient indépendamment associées à la MPC. Conclusions: La présence de MPC indique la nécessité d'un soutien thérapeutique supplémentaire aux jeunes vivant avec le VIH, à côté de à la fourniture de l'ART, pour assurer un âge adulte en meilleure santé.